Evaluating small‐scale simulation training of firearm safety to children with autism spectrum disorder. (16th April 2021) - Orner, Margaret E.; Miltenberger, Raymond G.; Maxfield, Trevor
Abstract: Every year children are unintentionally injured or killed due to finding an unattended firearm. Although research evaluating various approaches to teach safety skills shows that behavioral skills training and in situ training (IST) are effective, limited research exists evaluating small‐scale simulation training in teaching safety skills to children. Furthermore, there is no research evaluating this approach with children with autism spectrum disorder (ASD). This study evaluated the effectiveness of small‐scale simulation training in teaching firearm safety to 5–6‐year‐old children with ASD. Simulation training was effective for one participant, IST was necessary for one participant, and an incentive was required for the third participant to demonstrate the safety skills.